Actuator Fault Detection and Identification Using H-Infinity Filter - Ndabarushimana Egone; Ma Lei (IET Circuits, Devices and Systems)
Open-circuit faults (OCFs) in insulated gate bipolar transistors (IGBTs) within single-phase pulse width modulation (PWM) rectifiers can severely degrade system performance, leading to reduced output voltage, poor power quality, overheating, and safety risks, including electric shocks or fires. Reliable fault detection is critical for maintaining system efficiency and preventing further damage. This study presents an advanced fault detection method based on the H-infinity (H∞) approach, utilizing an extended H∞ filter to monitor system behavior and generate residual signals indicative of faults. The method effectively filters out external disturbances and system noise, minimizing false positives and enhancing detection accuracy. The proposed method was evaluated through hardware-in-the-loop (HIL) simulations that replicated real-world conditions of PWM rectifiers. Results show that the extended H∞ filter successfully detected OCFs with high accuracy and reduced false alarm rates. Performance metrics indicate a significant improvement in detection reliability compared to conventional methods. In conclusion, the H∞-based fault detection method offers a robust solution for real-time monitoring in power electronic systems. It enhances fault detection accuracy, reduces false alarms, and improves the operational safety and reliability of single-phase PWM rectifiers. Integrating this technique into power systems can mitigate risks associated with IGBT failures and ensure optimal performance under varying operational conditions.